Design and Construction of a 5 Kg Capacity Cracker Dough Mixer - Yadi Hikmah Setiana; Susilawati; Muhamad Kamaludin; Rian Dwi Aji Saputro; Nurizzi Rifqi Ferdian; Ari Setian (Politeknik Piksi Ganesha Indonesia, 2025)
This study developed a design for a dough mixer machine for cracker production with a capacity of 5 kg, intended to meet the needs of small to medium-scale production. The machine design incorporates stainless steel for parts that come into direct contact with food and hollow steel for the main frame to ensure both strength and hygiene. The single-phase motor used is tailored to the needs of small and medium enterprises to achieve optimal energy efficiency. The mixing blades are designed with a dual-blade system to enhance dough homogeneity in a short amount of time. The control panel, which includes a simple on/off switch and an emergency stop button, is ergonomically designed for ease of use by non-technical operators. The machine cleaning process is also simplified with a mixing container that can be opened or tilted, supporting cleanliness and speeding up the workflow. This design emphasizes efficiency, safety, and user comfort. The contribution of this research is expected to advance food machinery technology, particularly in cracker processing, and serve as a reference for the development of similar machines in the future.